2009
DOI: 10.1021/cm901956r
|View full text |Cite
|
Sign up to set email alerts
|

Zintl Chemistry for Designing High Efficiency Thermoelectric Materials

Abstract: Zintl phases and related compounds are promising thermoelectric materials; for instance, high zT has been found in Yb14MnSb11, clathrates, and the filled skutterudites. The rich solid-state chemistry of Zintl phases enables numerous possibilities for chemical substitutions and structural modifications that allow the fundamental transport parameters (carrier concentration, mobility, effective mass, and lattice thermal conductivity) to be modified for improved thermoelectric performance. For example, free carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
496
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 612 publications
(506 citation statements)
references
References 117 publications
8
496
0
2
Order By: Relevance
“…As a consequence, the thermal conductivity of skutterudites and clathrates can be reduced greatly while maintaining the electrical conductivity at a high level. Zintl compounds [7] with a large unit cell, including Yb 14 MnSb 11 , Yb 11 GaSb 9 , Ca 11 GaSb 9 and SrZnSb 2 have also been revealed to possess an intrinsically low lattice thermal conductivity due to the high fraction of low-velocity optical phonon modes [8]. In research on low-dimensional material systems, Dresselhaus et al [9] suggested that the power factor (α 2 σ) can be enhanced through the use of quantumconfi nement eff ects.…”
Section: Review Articlementioning
confidence: 99%
“…As a consequence, the thermal conductivity of skutterudites and clathrates can be reduced greatly while maintaining the electrical conductivity at a high level. Zintl compounds [7] with a large unit cell, including Yb 14 MnSb 11 , Yb 11 GaSb 9 , Ca 11 GaSb 9 and SrZnSb 2 have also been revealed to possess an intrinsically low lattice thermal conductivity due to the high fraction of low-velocity optical phonon modes [8]. In research on low-dimensional material systems, Dresselhaus et al [9] suggested that the power factor (α 2 σ) can be enhanced through the use of quantumconfi nement eff ects.…”
Section: Review Articlementioning
confidence: 99%
“…2,3 In particular, they benefit from extremely low lattice thermal conductivity resulting from their complex unit cells, 4 and their electronic properties can often be finely tuned using chemical substitutions. Excellent thermoelectric performance (zT > 1) has been demonstrated in several Zintl phases, 5 including Yb 14 MnSb 11 and YbZn 2−xCd x Sb 2 . 6,7 Many more Zintl phases, though not yet optimized for thermoelectric applications, appear to be promising candidates.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The TE performance of a material is characterized by its dimensionless thermoelectric figure of merit ZT = S 2 T/ρκ, where S is the Seebeck coefficient, T the absolute temperature, ρ the electrical resistivity, and κ the total thermal conductivity. Great effort has been expended in materials research and optimization utilizing the concepts of phonon-glass electron-crystal compounds (PGEC), [4][5][6] nano-inclusion materials, 7,8 and investigating compounds with complex crystal structures 9,10 with the goal of achieving high ZT TE materials.…”
Section: Introductionmentioning
confidence: 99%